MANAGEMENT OF VASCULAR WILT OF LENTIL THROUGH BIO CONTROL AGENTS AND ORGANIC AMENDMENTS IN TARAI AREA OF UTTARAKHAND STATE - KUMAR, VIJAY; GARKOTI , ANKITA; H. S. TRIPATHI (The Bioscan, 2013)
Lentil is an important component of farming systems in our country. It is one of the important and most nutritious rabi pulses. Lentil wilt caused by Fusarium oxysporum f.sp. lentis is a disease of national importance and it is a limiting factor to lentil cultivation. Field trials were carried out consecutively during Rabi 2007-08 and 2008-09 crop seasons in Randomized Block Design (RBD) with three replications, using popular variety Pant L-639. The plot size was 3.0×1.5m2 with row spacing of 30cm. It has been observed that seed treatment with Trichoderma harizanum + Pseudomonas fluorescence gave significant reduction in disease incidence and maximum grain yield. Among organic amendments cow dung manure, FYM, spent compost and vermicompost, minimum disease incidence 3.25% was observed in case of FYM treated plots followed by vermicompost (4.25%) and cow dung manure (4.75%). The highest disease incidence was recorded in spent compost amended plots (5.75%). Similarly highest grain yield in FYM (575 kg/ha) followed by vermicompost (525.5 kg/ha) and cow dung manure (475.5kg/ha).amended plots.